Estilos de aprendizaje y su incidencia en el rendimiento académico mediante un análisis comparativo de las modalidades virtual y presencial debido a las restricciones provocadas por pandemia. - Arévalo Flores, Yessenia Viviana (2023)
Understanding learning styles has been of paramount importance for the educational field, allowing teachers to create a more inclusive and equitable educational environment, where all students have the opportunity to learn effectively. It also helps students develop skills such as critical thinking, problem solving, and creativity. On the other hand, academic performance is an important indicator of a person's ability to acquire and apply knowledge and has a significant impact on their success in the workforce and in life. Therefore, this research was carried out with the aim of demonstrating whether learning styles had any influence on academic performance in biotechnology students within a virtual and later in-person academic context, because of confinement due to the health emergency (pandemic). The research had a quantitative approach, with a sample of 116 biotechnology students for data collection. The Learning Styles According to PNL, test was used as an instrument, which consists of 40 multiple choice questions, a survey to find out the degree of satisfaction of the students when they took their semester in virtuality, and for academic performance, the students' grades in both modalities were collected. As results, it was found that the predominant learning style was kinesthetic, in academic performance, it was possible to observe an obvious alteration in relation to the two modalities, and finally, in the satisfaction survey, students preferred the face-to-face modality for their career, and factors that affected their learning were evident.